On the empresses of the Latin Empire (1204–1261) (4). Berengaria of Léon - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2023)
This article is the fourth part of the series „On the Empresses of the Latin Empire (1204–1261)”. Its aim is to present the biography of Berengaria of León (Berenguela in Castilian), the third wife of John of Briene, mainly on the basis of Castilian and Old French sources. Information about her is laconic and scattered through various sources. Berengaria was the daughter of King Alfonso IV of Leon and his second wife, Berengaria of Castile. Born in 1204, in 1224 she married the former king of Jerusalem, John of Brienne. She became the Latin empress in 1231. She had three sons, her daughter Mary, as the wife of Baldwin II, also became the Latin empress, Little is known about Berengaria's education and her language skills during the stay in Constantinople. She died there in April 1237, but was buried in Compostela. She was not politically active and did not play a significant role in the history of the the Latin Empire.